A sign of the times: Catholic advocacy for social justice in Nkrumah's Ghana, 1958 - Jallow, Baba Galleh (The journal of religion & society, 2014)
The Ghana Catholic Church's advocacy for social justice predated Vatican II thanks to her early encounter with independence in 1957. Throughout 1958, the Church in Ghana engaged the government of Prime Minister Kwame Nkrumah in a robust dialogue on social justice. Through The Standard, her National Catholic weekly, the Church directed a steady stream of communication to the state on issues of social justice that approximate key lessons of Catholic Social Teaching on respect for human dignity and concern for truth and justice. The Ghana Church's advocacy for justice was a sign of the times that reflected the mind of Pope John XXIII and what happened at the Second Vatican Council.